Investigation on threshold power of stimulated Brillouin scattering in photonic crystal fiber - Parvizi, R.; Harun, Sulaiman Wadi; Ali, N.M.; Arof, Hamzah; Ahmad, Harith (ELSEVIER, 2012)
We have developed a theoretical approach to simulate stimulated Brillouin scattering (SBS) generation in photonic crystal fiber (PCF). The threshold condition for the SBS occurrence has been derived as a function of fiber parameters and input pump power. A particular emphasis is given to the influence of the input pump power and fiber length on the Brillouin gain in the PCF. To assess threshold pump power accurately, the pump depletion effect has been included by employing the 1% criterion. This simulation can anticipate the Brillouin threshold gain value precisely. The threshold gain varies from 14 to 18 depending on the PCF length.